IMPROVING STUDENTS’ READING SKILLS OF NARRATIVE TEXT USING SQ3R (SURVEY, QUESTION, READ, RECITE AND REVIEW) METHOD - Ma`la, Shofwatul (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This research deals with Improving Students’ Reading Skills Narrative Text Using SQ3R (Survey, Question, Read, Recite and Review) Method (Classroom Action Research of the Eleventh Graders at SMA Islam Sultan Agung 1 Semarang in the Academic Year 2023/2024). The population of this research is the students XI-9 Grader of SMA Islam Sultan Agung 1 Semarang, consisted of 25 students. In this research, the writer uses total sampling technique. The research collected data by using a test namely pre-test and post-test. The result shows that mean score in pre-test 62,8 and in post-test 87,6 show that the students’ ability before treatment is low but after giving treatment the students’ ability higher. It means that SQ3R Method is effective to improve the students’ ability in reading skill.